Wireless electromechanical enantio‐responsive valves. Issue 2 (13th December 2022) - Salinas, Gerardo; Malacarne, Filippo; Bonetti, Giorgia; Cirilli, Roberto; Benincori, Tiziana; Arnaboldi, Serena; Kuhn, Alexander
Abstract: Microfluidic valves based on chemically responsive materials have gained considerable attention in recent years. Herein, a wireless enantio‐responsive valve triggered by bipolar electrochemistry combined with chiral recognition is reported. A conducting polymer actuator functionalized with the enantiomers of an inherently chiral oligomer was used as bipolar valve to cover a tube loaded with a dye and immersed in a solution containing chiral analytes. When an electric field is applied, the designed actuator shows a reversible cantilever‐type deflection, allowing the release of the dye from the reservoir. The tube can be opened and closed by simply switching the polarity of the system. Qualitative results show the successful release of the colorant, driven by chirality and redox reactions occurring at the bipolar valve. The device works well even in the presence of chemically different chiral analytes in the same solution. These systems open up new possibilities in the field of microfluidics, including also controlled drug delivery applications. Abstract : Bipolar enantioselective valves allow controlling the release of molecules from a reservoir as a function of the chirality of the stereoisomers present in the surrounding solution.